Understanding willingness to communicate in L2 between Korean and Taiwanese students. (May 2022) - Lee, Ju Seong; Lee, Kilryoung; Chen Hsieh, Jun
This study examined Korean ( n = 143) and Taiwanese ( n = 261) EFL students' willingness to communicate in a second language (L2 WTC) in in-class, out-of-class, and digital settings. Follow-up interviews ( n = 20) were also conducted to identify factors that might have influenced their L2 WTC. Results showed that Korean and Taiwanese participants scored lowest on L2 WTC inside the classroom. The qualitative data suggest that L2 speaking anxiety might have equally influenced both groups' L2 WTC. Additionally, while Korean students scored higher on L2 WTC outside the classroom than Taiwanese students, the Taiwanese scored higher on L2 WTC in digital settings than did the Koreans. The qualitative data revealed that these discrepancies might have been influenced by English environment and teaching practice. These findings suggest that East Asian learners of English as a foreign language (EFL) can become more willing to communicate when sufficient opportunities for English use are provided through instructional and institutional support.